2020
DOI: 10.1101/2020.04.09.033910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative Network Biology Framework Elucidates Molecular Mechanisms of SARS-CoV-2 Pathogenesis

Abstract: COVID-19 (Coronavirus disease 2019) is a respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). While the pathophysiology of this deadly virus is complex and largely unknown, we employ a network biology-fueled approach and integrated multiomics data pertaining to lung epithelial cells-specific coexpression network and human interactome to generate Calu-3-specific human-SARS-CoV-2 Interactome (CSI). Topological clustering and pathway enrichment analysis show that SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Intriguingly, all the 16 hub genes are targets of more than one SARS-CoV-2 protein (Table 1 ), out of which NPM1, SNW1, GRB2, HSP90AA1, and ELAVL1 are the target of several SARS-CoV-2 proteins. These findings are consistent with previous findings which indicates that an individual viral protein can target multiple host proteins and several viral proteins can interact with the same host protein [ 25 , 26 , 55 57 ].…”
Section: Resultssupporting
confidence: 93%
“…Intriguingly, all the 16 hub genes are targets of more than one SARS-CoV-2 protein (Table 1 ), out of which NPM1, SNW1, GRB2, HSP90AA1, and ELAVL1 are the target of several SARS-CoV-2 proteins. These findings are consistent with previous findings which indicates that an individual viral protein can target multiple host proteins and several viral proteins can interact with the same host protein [ 25 , 26 , 55 57 ].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, integration of drug-target networks of the top 16 drug candidates produced of potent drug combinations using a complementary exposure technique (Chen et al, 2020b). Other studies have also shown the potential of using a network based methodology to screen possible drug targets for SARS-CoV-2 (Hofmarcher et al, 2020;Kumar et al, 2020;Li et al, 2020c).The method is a quick way of identifying drug targets. However, it is not designed to produce drugs, but is a useful tool for prediction of new drugs, and combinations, and reduces the period of drug screening and development.…”
Section: Network-based Methods For Prediction Of Drug-target Interactmentioning
confidence: 99%
“…As it is the case of Giotis et al [ 52 ], these studies often involve global transcriptome analyses, via RNA-seq or microarrays, together with computational efforts, which intend to screen the key elements of the immune system that are required for the appropriate response. This approach ultimately leads experimental research through predictive analyses, as in the case of co-expression gene networks [ 53 ].…”
Section: Related Workmentioning
confidence: 99%